1999
DOI: 10.1038/21202
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of vancomycin tolerance in Streptococcus pneumoniae

Abstract: Streptococcus pneumoniae, the pneumococcus, is the most common cause of sepsis and meningitis. Multiple-antibiotic-resistant strains are widespread, and vancomycin is the antibiotic of last resort. Emergence of vancomycin resistance in this community-acquired bacterium would be catastrophic. Antibiotic tolerance, the ability of bacteria to survive but not grow in the presence of antibiotics, is a precursor phenotype to resistance. Here we show that loss of function of the VncS histidine kinase of a two-compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
260
2
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(275 citation statements)
references
References 25 publications
5
260
2
4
Order By: Relevance
“…The recent model suggested that Pep27, encoded upstream of the VncRS locus was secreted from the cell by the Vex123 transporter [14]. In this study, we elucidated the underlying immunological processes and identified VncRS, which is the vancomycin-resistant TCS [15] in serotype 2 of the D39 strain, to be responsible for fulminant inflammation and sepsis in mice, and as a key factor for lysis and sepsis. We additionally identified that mutations in pep27 VncRS abrogate inflammation and sepsis.…”
Section: Introductionmentioning
confidence: 94%
“…The recent model suggested that Pep27, encoded upstream of the VncRS locus was secreted from the cell by the Vex123 transporter [14]. In this study, we elucidated the underlying immunological processes and identified VncRS, which is the vancomycin-resistant TCS [15] in serotype 2 of the D39 strain, to be responsible for fulminant inflammation and sepsis in mice, and as a key factor for lysis and sepsis. We additionally identified that mutations in pep27 VncRS abrogate inflammation and sepsis.…”
Section: Introductionmentioning
confidence: 94%
“…This mutation was thought to be the main mechanism behind vancomycin tolerance leading to autolytic activity suppression. A study conducted in the late 1990s reported that the vncS mutant not only exhibited vancomycin tolerance, but also was capable of developing tolerance to many other antibiotics, including quinolones and beta-lactams [65].…”
Section: Fluoroquinolone (Fq) Resistancementioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18] In the research of multivalency, the ligandreceptor pair of vancomycin (Van)-D-Ala-D-Ala has attracted a great deal of research attention because it relates to vancomycin [19][20][21][22] -resistant enterococci (VRE). 23, 24 Walsh and colleagues 21,[24][25][26][27] have deciphered the mechanism of vancomycin resistance: VRE mutates its terminal peptides from D-Ala-D-Ala to D-Ala-D-Lac (i.e., D-alanine-D-lactate), which has substantially lowered (∼10 3 times decrease) its affinity to Van. 25,26,28 Though Van self-associates to form homodimers upon binding to D-Ala-D-Ala, as elucidated by Williams et al, [29][30][31][32][33] this noncovalent dimerization of Van alone is insufficient to act against VRE.…”
Section: Introductionmentioning
confidence: 99%